2018
DOI: 10.1055/s-0038-1677391
|View full text |Cite
|
Sign up to set email alerts
|

Prognostische Bedeutung sonographischer Parameter der Pankreatitis der Katze

Abstract: Zusammenfassung Gegenstand: Die feline Pankreatitis ist eine Erkrankung mit sehr unterschiedlichen klinischen Verlaufsformen. Häufig stellt sich die Frage, inwieweit Parameter der klinischen, labordiagnostischen oder bildgebenden Untersuchungsverfahren zur Früherkennung eines progressiven, mit schlechterer Prognose verbundenen Verlaufs verwendet werden können. Nur wenige Studien untersuchten bei dieser Erkrankung prognostische Faktoren. Bei Vorliegen passender klinischer Symptomen dienen vor allem di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Several studies have reported that Spec fPL assay is clinically useful. 8,9,[11][12][13] The results of this study suggest that the use of a decision threshold of 8.8 μg/L would have high diagnostic specificity for excluding clinically healthy cats. Further studies evaluating the clinical utility of Spec fPL with the revised reference interval and decision threshold as a cutoff for diagnosing feline pancreatitis are warranted.…”
Section: Con Clus Ionsmentioning
confidence: 76%
See 3 more Smart Citations
“…Several studies have reported that Spec fPL assay is clinically useful. 8,9,[11][12][13] The results of this study suggest that the use of a decision threshold of 8.8 μg/L would have high diagnostic specificity for excluding clinically healthy cats. Further studies evaluating the clinical utility of Spec fPL with the revised reference interval and decision threshold as a cutoff for diagnosing feline pancreatitis are warranted.…”
Section: Con Clus Ionsmentioning
confidence: 76%
“…8 The reported sensitivity varies from 42% to 79%, with a reported specificity from 63% to 100%. [8][9][10][11][12][13] The variation of the sensitivity and specificity might partly be due to differences in study design. Serum lipase activity, as measured by assays using 1,2-o-dilauryl-rac-gly cero-3-glutaric acid-(6′-methylresorufin) ester (DGGR) as a substrate, has been evaluated for its diagnostic utility in pancreatitis in cats and was shown to have a good agreement with the Spec fPL assay.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retrospective studies have identified a history of weight loss, lower body weight at presentation, lethargy, persistent anorexia during hospitalization, pleural effusion, dyspnea, parenteral nutrition, hypocalcemia, hyperkalemia, hypoglycemia, azotemia, an elevated Spec fPL concentration, and an absence of antimicrobial therapy as negative prognostic/severity indicators in cats with pancreatitis [ 2 , 8 , 9 , 10 , 11 ]. With regard to diagnostic imaging, a recent retrospective study in Germany determined that the presence and severity of pancreatic ultrasound abnormalities were not associated with outcome in cats with pancreatitis [ 12 ]. Pancreatitis in cats is commonly associated with chronic enteropathy and cholangitis, suspected to be related to the anatomical configuration of the major pancreatic duct and duodenal papilla in cats [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%